TERAPI SEFT (SPIRITUAL EMOTIONAL FREEDOM TECHNIQUE) UNTUK MENGATASI KECEMASAN BELAJAR SISWA: Volume 3 No 2 Juli 2022 - Khairul Annuar; Nurus Saadah (Fakultas Agama Islam Universitas Wiralodra, 2022)
Today many students experience anxiety in learning. Learning anxiety is a psychological and physiological condition characterized by a sense of discomfort in cognitive, emotional and behavioral manifestations.Anxiety with a reasonable intensity can be considered to have a positive value as motivation, but if the intensity is very strong and negative, it will actually cause harm and can interfere with the physical and psychological conditions of the individual concerned. If the individual responds to anxiety irrationally, then the individual always feels anxious about his or her inability to complete certain tasks.Therefore, efforts to prevent or minimize student anxiety are through the emotional freedom technique. The working principle of the Emotional freedom technique is to harmonize and restore the disturbed energy system in the body, through stimulation of the body's energy points known as meridians by tapping (light tapping). The procedure for emotional freedom technique is the set up (the set up words), the tune-in, the tapping, the nine gamut procedure and the tapping again.This study aims to determine how the application of SEFT to students who have learning anxiety, the method used in this study is the literature review method.